Convection-Enhanced Delivery of a First-in-Class Anti-β1 Integrin Antibody for the Treatment of High-Grade Glioma Utilizing Real-Time Imaging - Chibueze D. Nwagwu; Amanda V. Immidisetti; Gabriela Bukanowska; Michael A. Vogelbaum; Anne-Marie Carbonell (MDPI AG, 2020)
Introduction: OS2966 is a first-in-class, humanized and de-immunized monoclonal antibody which targets the adhesion receptor subunit, CD29/β1 integrin. CD29 expression is highly upregulated in glioblastoma and has been shown to drive tumor progression, invasion, and resistance to multiple modalities of therapy. Here, we present a novel Phase I clinical trial design addressing several factors plaguing effective treatment of high-grade gliomas (HGG). Study Design: This 2-part, ascending-dose, Phase I clinical trial will enroll patients with recurrent/progressive HGG requiring a clinically indicated resection. In Study Part 1, patients will undergo stereotactic tumor biopsy followed by placement of a purpose-built catheter which will be used for the intratumoral, convection-enhanced delivery (CED) of OS2966. Gadolinium contrast will be added to OS2966 before each infusion, enabling the real-time visualization of therapeutic distribution via MRI. Subsequently, patients will undergo their clinically indicated tumor resection followed by CED of OS2966 to the surrounding tumor-infiltrated brain. Matched pre- and post-infusion tumor specimens will be utilized for biomarker development and validation of target engagement by receptor occupancy. Dose escalation will be achieved using a unique concentration-based accelerated titration design. Discussion: The present study design leverages multiple innovations including: (1) the latest CED technology, (2) 2-part design including neoadjuvant intratumoral administration, (3) a first-in-class investigational therapeutic, and (4) concentration-based dosing. Trial registration: A U.S. Food and Drug Administration (FDA) Investigational New Drug application (IND) for the above protocol is now active.